An Overview of Ovarian Tumours at B.P. Koirala Memorial Cancer Hospital, Nepal - Pun, Chin Bahadur; Shrestha, Sadina; Bhatta, Ranjan Raj; Pandey, Greta; Uprety, Suraj; Bastakoti, Shankar; Dhungana, Ishan; Jha, Nandita; Xiufang, Guo; Lei, Wang (Nepalese Journal of Cancer, 2019)
Introduction: Ovarian cancer is the seventh most commonly diagnosed cancer among women in the world. This study was conducted with the aim to find out different histological types of ovarian tumours reported at B.P. Koirala Memorial Cancer Hospital (BPKMCH), Chitwan, Nepal. Methods: This was a retrospective study carried out at the Department of Pathology of BPKMCH from January 1, 2018 to December 31, 2018. This study included the patients who were operated at BPKMCH or referred cases from elsewhere, but the specimen was processed and reported at BPKMCH. All the data were retrieved and analyzed from the records of Pathology Department. Results: Altogether 87 cases of ovarian tumours were reported during the study period. Out of which, 31 cases were benign ovarian tumours whereas 56 cases were malignant ovarian tumours. Both benign and malignant ovarian tumours were most common in age group 41 to 50 years of age. Among benign ovarian tumours, 12 cases were serous cystadenoma, 7 cases mucinous cystadenoma, 6 cases mature cystic teratoma, 2 cases serous cyst adenofibroma, 2 cases benign Brenner tumour and 2 endometroid cystadenoma. Among malignant ovarian tumours, 33 cases were serous cystadenocarcinoma, 11 cases mucinous cystadenocarcinoma, 2 cases immature teratoma, 3 cases were malignant sex cord stromal tumours (granulosa cell tumour), 2 cases dysgerminoma, 1 case yolk sac tumour, 1 case endometroid carcinoma and 3 cases were metastatic adenocarcinoma. Conclusion: Surface epithelial tumours were most common ovarian tumours in this study. Serous cystadenomas were most common benign ovarian tumours whereas serous cystadenocarcinomas were the most common malignant ovarian tumours.